Islam as a Condition for Waqf: Dialectics of Classical Fiqh and Indonesian Waqf Law in a Pluralistic Society - Hilmi Marwa Abdullah; Musyafi Usman; Sadida Nizam; Muhammad Bilal (Yayasan Cendekia Gagayunan Indonesia, 2025)
Waqf plays a strategic role in strengthening the Islamic economy and promoting social welfare. However, scholarly debate persists regarding whether being Muslim constitutes a substantive legal requirement for a waqif, particularly within Indonesia’s pluralistic socio-legal context. Existing studies largely focus on administrative or economic aspects of waqf, while the normative tension between classical Islamic jurisprudence and Indonesian positive law on the religious status of the waqif remains underexplored. This study aims to address this gap by critically examining the requirement of Islamic faith for waqif from the perspectives of Islamic jurisprudence and Indonesian waqf law. Employing a qualitative normative-juridical method, the research analyzes classical and contemporary fiqh sources from the four Sunni schools (Ḥanafī, Mālikī, Syāfi‘ī, and Ḥanbalī), alongside national regulations, particularly Law No. 41 of 2004 on Waqf and Government Regulation No. 42 of 2006. The findings demonstrate that, within Islamic jurisprudence, being Muslim is not an absolute prerequisite for the validity of waqf, except when the object of waqf is directly related to ritual worship, such as mosques. The Ḥanafī, Syāfi‘ī, and Ḥanbalī schools emphasize legal capacity (ahliyyah al-taṣarruf), ownership, and lawful objectives as determining factors of validity. Similarly, Indonesian waqf law does not impose religious restrictions on waqif, provided that the waqf serves public benefit and does not contradict sharia principles. This study contributes to the discourse on waqf law by demonstrating that the requirement of Islam for waqif functions as a contextual moral and spiritual value rather than a rigid juridical condition, thereby highlighting a normative convergence between classical fiqh and national law in prioritizing social justice and public welfare.